(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2025)
This research aims to explore the ways that Saudi male and female PhD students write their requests to potential PhD supervisors in Australia. While other studies of request analysis are generally more categorical, the current project is more concerned with the way requests by Saudi men and women are made. The authors, using DCTs, have come up with results that do not reflect the real gender differences in requesting behavior. In contrast, this research is an extension of contextualism, or rather, an emphasis on contextual aspects of speech acts, which corresponds to the idea that they have a major degree of dependence from context on interaction (House & Kádár, 2023). A total of 120 authentic emails, 120 from 120 participants equally divided into five male Saudis and five female Saudis, along with five male Anglo-Saxon representatives from the Anglo-Saxon sample, formed the database for gender research in Saudi Arabia. Methodologically, it merges selective pragmatic frameworks, from first-order politeness analyses, second-order analyses, to third-order analyses of politeness (House & Kádár, 2023). The findings provide a counterpoint to the stereotype of expecting the gender- and cultural difference in requesting behavior. This also offers an important case for future research on how to observe these distinctions. In this study, cultural and situational considerations play a pivotal role in the research on speech acts. Finally, it would have implications for scholars and practitioners working in the field of pragmatics.